Urban art and neighborhood-brand identity: The case of Lavapiés and its representation on Instagram - Urquía Uriaguereca, Íñigo (Street Art & Urban Creativity, 2025)
This study examines how urban art, through UGC (User Generated Content) on Instagram, contributes to the creation of a neighborhood's place brand identity. Focusing on the Lavapiés neighborhood in Madrid (Spain), a content analysis was conducted on posts tagged with #Lavapiés. The results reveal that urban art is the most frequent theme in the posts, highlighting its primary connection with the gastronomy and the social life of the neighborhood. However, a significant disconnection between urban art and political or civic participation is observed, suggesting an assimilation of this type of art into everyday life, distancing it from its potentially subversive nature. The study concludes with a reflection on the underestimated role of institutions in shaping the place brand.